1982
DOI: 10.1002/j.1537-2197.1982.tb13230.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure of Mistletoe Pollen. Iv. Eurasian and Australian Viscum L. (Viscaceae)

Abstract: Fifteen Eurasian and Australian species of Viscum L. were examined by light, scanning, and transmission electron microscopy. Pollen characters divide the species into two groups, each correlated with differences in habit and inflorescence structure: Group I (12 spp.) characterized by psilate or slightly sculptured exines and a non‐uniform ektexine pattern and Group II (3 spp.) possessing highly sculptured (echinate, rodlet) surfaces and uniform ektexine patterns. Within each of the groups, pollen characters di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…The outstanding work on the pollen morphology of extant Loranthaceae by Feuer & Kuijt (1979 , 1980 , 1985 ) and other Santalales lineages ( Maguire, Wurdack & Huang, 1974 ; Feuer, 1977 , 1978 , 1981 ; Feuer & Kuijt, 1978 , 1982 ; Feuer, Kuijt & Wiens, 1982 ) demonstrated that most pollen produced by members of the Loranthaceae cannot be confused with pollen from other angiosperm families ( Grímsson, Grimm & Zetter, 2017 ). Grímsson, Grimm & Zetter (2017) distinguished four general types (Pollen Type A, B, C, D), of which only one (Pollen Type A) could be confused with pollen of other Santalales lineages, and would unlikely be recognised as Loranthaceae pollen if found in a fossil pollen sample.…”
Section: Introductionmentioning
confidence: 99%
“…The outstanding work on the pollen morphology of extant Loranthaceae by Feuer & Kuijt (1979 , 1980 , 1985 ) and other Santalales lineages ( Maguire, Wurdack & Huang, 1974 ; Feuer, 1977 , 1978 , 1981 ; Feuer & Kuijt, 1978 , 1982 ; Feuer, Kuijt & Wiens, 1982 ) demonstrated that most pollen produced by members of the Loranthaceae cannot be confused with pollen from other angiosperm families ( Grímsson, Grimm & Zetter, 2017 ). Grímsson, Grimm & Zetter (2017) distinguished four general types (Pollen Type A, B, C, D), of which only one (Pollen Type A) could be confused with pollen of other Santalales lineages, and would unlikely be recognised as Loranthaceae pollen if found in a fossil pollen sample.…”
Section: Introductionmentioning
confidence: 99%